Interaction of State and Public Structures in The Field of Legal Aid - Burlachenko Petro Dmytrovych (Emerging Frontiers Library for The American Journal of Political Science Law and Criminology, 2025)
The article presents an analysis of the interaction between state and public structures in the field of legal assistance to ensure access to justice for socially vulnerable groups. In this article, the mechanisms of cooperation, barriers, and strategies to enhance effectiveness under conditions of intensified social stratification and legal complexity will be examined. The relevance of this work can be attributed to the enormous scale of the problem: 5 billion people lack access to justice, and 92% of low-income Americans face unresolved legal issues. The methodological framework employed here comprises a comparative analysis of three legal systems (India, the USA, and Australia), conducted through a systematic review of 13 sources (international acts, statistics, and cases), supplemented by content data evaluation. It was observed that state aid governed by statutes provides fundamental support. However, it comes with bureaucracy and underfunding. Key findings underscore the need for reforms that can fundamentally eliminate systemic barriers. Major issues include gender differences, significant delays in immigration courts, and insufficient free assistance. The successful plans that halted large evictions by teaming up in the Right to Counsel program in New York City reveal something else. Suggestions include more cash, online help, law school, and focused things for weak people (like migrants and ethnic groups). This article is useful for attorneys, human rights advocates, lawmakers, and scholars who want to promote justice, access, and social fairness.